Self-assessment in educational centres - Laorden Gutiérrez, Cristina (Pulso. Revista de educación, 2004)
This article emphasises the significance of conducting internal evaluations of educational institutions, which serve a dual purpose of facilitating collective reflection about all elements of the community and fostering individual reflection among education professionals.  The article presents compelling data that urges us to examine and consider the concept of self-assessment, which is increasingly gaining prominence in the educational process. It explains self-assessment as a process that presents numerous opportunities for enhancing education and highlights certain challenges associated with its implementation.